KEPEMIMPINAN VISIONER KEPALA SEKOLAH DALAM MERUMUSKAN SEKOLAH DASAR RAMAH ANAK DAN INKLUSIF DI KOTA BIMA - Ikhsan Maulana; Harun Joko Prayitno; Bambang Sumardjoko (STKIP Subang, 2026)
This study aims to explore and analyze the leadership style of school principals who are oriented towards the formation of a supportive educational environment for all students, especially for children with special needs. The method used in this study is a qualitative study with a descriptive approach. The data collection technique was carried out through in-depth interviews and observations in several elementary schools in Bima City, which were then analyzed using thematic analysis. The results show that visionary principals are able to integrate inclusive and child-friendly values into school policies and practices, as well as motivate teachers and staff to collaborate in creating a conducive learning environment. These findings make a significant contribution to the development of school leadership models that are more adaptive and responsive to the needs of all students, as well as underscore the importance of leadership that puts students at the center of the learning process. The conclusions of this study reflect that effective visionary leadership not only drives academic achievement but also creates an inclusive and child-friendly school culture.